Associations between pretreatment nutritional assessments and treatment complications in patients with stage I-III non-small cell lung cancer: A systematic review. (February 2022) - Voorn, M.J.J.; Beukers, K.; Trepels, C.M.M.; Bootsma, G.P.; Bongers, B.C.; Janssen-Heijnen, M.L.G.
Summary: Background: Patients with stage I-III non-small cell lung cancer (NSCLC) are often nutritionally depleted and therefore at high-risk for treatment complications. Identifying these patients before the start of treatment is important to initiate preventive interventions for better treatment outcomes. This study aimed to evaluate which outcome variables of pretreatment nutritional assessments are associated with posttreatment complications in patients with stage I-III NSCLC, as well as to identify cut-off values for clinical risk stratification. Methods: In this systematic review, PubMed, Embase, and Cinahl databases were searched for eligible studies published up to March 2021. Studies describing the association between pretreatment nutritional assessment and treatment complications in patients with NSCLC were included. Methodological quality of the included studies was assessed using the Newcastle–Ottawa Scale for cohort studies. Results: A total of 23 studies were included, which merely focused on surgical treatment for NSCLC. Methodological quality was poor in thirteen studies (57%). Poor outcomes of body mass index, sarcopenia, serum albumin, controlling nutritional status, prognostic nutrition index, nutrition risk score, and (geriatric) nutrition risk index were associated with a higher risk for treatment complications. Cut-off values for pretreatment nutritional assessment were reported in a limited number of studies and were inconsistent. Conclusion: Poor outcomes of pretreatment nutritional assessments are associated with a higher risk for posttreatment complications. Further research is needed on the ability of easy-to-use pretreatment nutritional assessments to accurately identify patients who are at high risk for treatment complications, as high-risk patients may benefit from pretreatment interventions to improve their nutritional status. Graphical abstract: Image 1